2017
DOI: 10.1192/bjp.bp.116.189464
|View full text |Cite|
|
Sign up to set email alerts
|

Association between mental health-related stigma and active help-seeking: Systematic review and meta-analysis

Abstract: Mental disorders create high individual and societal costs and burden, partly because help-seeking is often delayed or completely avoided. Stigma related to mental disorders or mental health services is regarded as a main reason for insufficient help-seeking.To estimate the impact of four stigma types (help-seeking attitudes and personal, self and perceived public stigma) on active help-seeking in the general population.A systematic review of three electronic databases was followed by random effect meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
365
2
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(405 citation statements)
references
References 111 publications
24
365
2
14
Order By: Relevance
“…Although approximately one‐third of caregivers with high depression symptoms and who were underprepared and a nearly a half of those with anxiety symptoms reported that they were interested in receiving support services, approximately three‐quarters to a half did not express interest. This discrepancy between apparent need and interest in services was especially pronounced relative to receipt of “counseling and therapy.” This is likely in part due to several issues including a well‐documented stigma against mental health services, including among cancer family caregivers . Second, caregivers may feel guilty about focusing on their own needs believing that it is at the expense of patients' needs .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although approximately one‐third of caregivers with high depression symptoms and who were underprepared and a nearly a half of those with anxiety symptoms reported that they were interested in receiving support services, approximately three‐quarters to a half did not express interest. This discrepancy between apparent need and interest in services was especially pronounced relative to receipt of “counseling and therapy.” This is likely in part due to several issues including a well‐documented stigma against mental health services, including among cancer family caregivers . Second, caregivers may feel guilty about focusing on their own needs believing that it is at the expense of patients' needs .…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy between apparent need and interest in services was especially pronounced relative to receipt of "counseling and therapy." This is likely in part due to several issues including a well-documented stigma against mental health services, 35 including among cancer family caregivers. 36 Second, caregivers may feel guilty about focusing on their own needs believing that it is at the expense of patients' needs.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma has been previously associated with a number of adverse outcomes on different aspects of well-being and quality of life. One possible explanation is that individuals who experience stigma are less likely to seek professional help or support (Schnyder, Panczak, Groth, & Schultze-Lutter, 2017). This may contribute to accessing less resources that could ameliorate their physical or/and psychological well-being.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…"Pathways to care" studies have long been shown to represent an effective and inexpensive method to characterize the help-seeking behaviour of those suffering from severe illnesses with longitudinal course in various fields of medicine (Campbell, Hotchkiss, Bradshaw, & Porteous, 1998;Rogler & Cortes, 1993). The evaluation of pathways to care in mental health is particularly necessary, also in consideration of the high level of stigma attached to mental illnesses and the difficulties that psychiatric patients experience when accessing psychiatric care (Thornicroft et al, 2009;Schnyder, Panczak, Groth, & Schultze-Lutter, 2017).…”
Section: Introductionmentioning
confidence: 99%